The Use of Textbook Entitled â€œLetâ€™s Learn Englishâ€: Teacherâ€™s overview - Muktamir Muktamir (IKIP PGRI Bojonegoro, 2020)
Abstract: Although there are some research revealing the evaluation of textbook used by the teacher, but a study investigating the use of textbook entitled â€œLetâ€™s Learn Englishâ€ as an instructional material viewed from teachers point of view were rare in number. The current study aimed at investigating the the use of textbook entitled â€œLetâ€™s Learn Englishâ€ as instructional material viewed from teacherâ€™s perspective as the user. This study used the qualitative case study. The case study was intended to analyze the use of textbook entitled â€œLetâ€™s Learn Englishâ€. The participants of this study was the teacher as the user. Text book analysis used was adapted from Mukundan & Nimehchisalem (2010). The results revealed that textbook entitled â€œLetâ€™s Learn Englishâ€ is applicable as an instructional material. Further research in evaluating the effectiveness of textbook entitled â€œLetâ€™s Learn Englishâ€ should be taken into account by the related parties. Â  Keywords: textbook evaluation, Textbook entitled â€œLetâ€™s Learn Englishâ€ Â  Abstrak: Meskipun terdapat beberapa penelitian mengkaji tentang evaluasi buku teks yang digunakan oleh guru, namun sebuah penelitian yang bertujuan menginvestigasi penggunaan buku teks berjudul â€œLetâ€™s Leran Englishâ€sebagai sumber pembelajaran dilihat dari sudut pandang guru belum pernah dilkasanakan. Penelitian ini bertujuan untuk menginvestigasi penggunaan buku teks berjudul â€œLetâ€™s Learn Englishâ€ sebagai sumber bahan ajar dilihat dari sudt pandang pendapat guru sebagai pengguna. Penelitian ini menggunakan metode kulaitatif studi kasus. Penelitian studi kasus bertujuan utuk menganalisis penggunaan buku teks berjudul Letâ€™s Learn Englishâ€. Partisipan dalam penelitian ini adalah guru sebagai pengguna. Dalam analisis buku teks ini menggunakan analisis buku teks nya (Mukundan & Nimehchisalem, 2010). Hasil dari penelitian ini menunjukkan bahwa buku teks berjudul Letâ€™s Leran English dapat digunakan sebagai sumber bahan ajar. Penelitian lanjutan tentang efektifitas dari buku teks berjudul â€œâ€Letâ€™s Leran Englishâ€ dapat menjadi perhatian khusus bagi semua kalangan. Â  Kata kunci: evaluasi buku teks, Letâ€™s Learn English